2008
DOI: 10.1111/j.1469-1795.2008.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling population viability of captive elephants in Myanmar (Burma): implications for wild populations

Abstract: Captive Asian elephants Elephas maximus, used as work animals, constitute up to 22-30% of remaining Asian elephants. Myanmar has the largest captive population worldwide ($6000), maintained at this level for over a century. We used published demographic data to assess the viability of this captive population. We tested how this population can be self-sustained, how many elephants must be supplemented from the wild to maintain it, and what consequences live capture may have for Myanmar's wild population. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
124
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(130 citation statements)
references
References 11 publications
3
124
3
Order By: Relevance
“…Parameters for the 7 scenarios were determined from the Lao national elephant registration database and other published demographic data (Lair 1997, Leimgruber et al 2008, ElefantAsia 2012 (Table 1). From the database we were able to accurately specify vital parameters, such as elephant age, sex and initial population size.…”
Section: Baseline Parameters For Pva Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…Parameters for the 7 scenarios were determined from the Lao national elephant registration database and other published demographic data (Lair 1997, Leimgruber et al 2008, ElefantAsia 2012 (Table 1). From the database we were able to accurately specify vital parameters, such as elephant age, sex and initial population size.…”
Section: Baseline Parameters For Pva Scenariosmentioning
confidence: 99%
“…Following Leimgruber et al (2008), the age of first offspring and the mortality rates for bulls and cows were considered to be alike, since we did not wish to overstate the rate of extinction. We used infant mortality rates based on Leimgruber et al (2008) for captive elephants rather than wild elephant mortality rates indicated by Armbruster et al (1999) or wild elephant mortality rates for Sri Lankan populations (Sukumar 2003).…”
Section: Baseline Parameters For Pva Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…Piper and Cranbrook (2007) propose the reintroduction of the Malayan tapir to the Planted Forest Zone in Sarawak, which consists of 490,000 ha of primary, secondary and industrial plantation forests, while several projects are attempting to re-establish orangutans in areas from which they have been extirpated (Corlett 2009a). With an estimated 16,000 captive elephants in Asia and many of these unwanted as their use in logging declines, the major problem with the Asian elephant is a lack of suitable habitat, rather than a shortage of animals for release (Leimgruber et al 2008). In contrast, both species of forest rhinoceros are critically endangered and neither has a captive population.…”
mentioning
confidence: 99%